The Polymorphism Function of Protamine 1 Gene and Some Immunological Factors in Sterile Couples - Thaer Ali Hussein, (University of Thi-Qar Journal of Science, 2023)
Background:Infertility is a global problematic that impacts nearly 15% of all couples, and is definite as, incapability to conceive following 12 months of freecontraceptive un-protected interaction. Material and methodology:serum OD of anti-follicle hormone as stimulation antibody and anti-sperm antibody was identifiedthrough assay method of enzyme–linked immune-sorbent. One Protamine 1gene polymorphic sites was genotyped on 72couple’s Sterility. Other 20 couples group was obviously healthy ones. Genotypes were assessed through (PCR-RFLP) method.Results: Regarding the Serum positivity of anti-sperm antibody and anti-follicle stimulation hormone antibody inperipheral blood of sterile couples.The results observed significant association between anti-sperm antibody, anti-folliclestimulation hormone antibody and sterile women (P value 0.18, 0.32 respectively), while non-significant for anti-spermantibody in sterile males P value (0.129), the reported SNP frequency was of no significance difference in comparison tomales of normal fertility, that propose that the SNP might not aid as a good molecular genetic diagnosis indicator for malessterility (MI). Conclusions: The SNP G197T are absent totally and are not related to MI with above-mentioned, thus such SNPs might notsignify as a molecular indicator for the MI genetic cause diagnosis in the current population of the study.